(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Digital health refers to the application of various technologies with the aim of supporting/offering healthcare services. Among such technologies, AI poses new regulatory challenges. This article aims at clarifying, in the light of the EU legislation, whether such technologies shall be considered medical devices, and which law applies to the various phases of their lifecycle. In this regard, the provisions of the relevant pieces of EU legislation (the Medical Device Regulation, the legislation on clinical trials of medicines, and the recent Commission’s proposal for an AI Act) will be coordinated, to identify the rules applicable to AI-based MDs overall and the requirements that the economic actors involved in their lifecycle shall comply with.